Early life diet containing prebiotics and bioactive whey protein fractions increased dendritic spine density of rat hippocampal neurons. Issue 55 (4th September 2016) - Waworuntu, Rosaline V.; Hanania, Taleen; Boikess, Steven R.; Rex, Christopher S.; Berg, Brian M.
Abstract: Early life nutrition plays an important role in brain development. Emerging research in rodents, piglets and humans suggest that prebiotics, milk fat globule membrane and lactoferrin may each play unique roles in brain development and cognitive functions. However, knowledge of their combined impact is lacking. We show here that providing weanling rats with a diet containing milk fat globule membrane, lactoferrin and a polydextrose/galactooligosaccharide prebiotic blend led to a significant increase in total dendritic spine density in hippocampal dentate gyrus neurons. Region‐specific alterations in dendritic spine density and morphology could provide a mechanistic basis underlying broader cognitive benefits, but further research is required to demonstrate functional consequences of these observations.